Fungsi dan Ragam Bahasa Indonesia - Nur Hasirah; Rahma Ashari Hamzah; Candra Aprisal (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to describe the role and variation of Indonesian language used in various communication contexts. The focus of the study is how Indonesian language functions as an efficient communication medium and how language variation is adjusted to conditions, goals, and conversation partners. This study applies a qualitative descriptive approach with observation, interview, and documentation methods as a means of data collection. Data sources are obtained from language use in educational environments, mass media, and the wider community. The results of the study indicate that Indonesian language has instrumental, regulatory, interactional, personal, heuristic, imaginative, and representational functions. In addition, the language variations found include formal, non-formal, spoken, and written variations, each of which is applied according to the social and situational context. These findings show how important it is to understand the function and variation of language in improving language competence appropriately and effectively.